Nonlinear interaction of waves in a hot inhomogeneous magnetized plasma - Tara Prasad Khan; Mahadeb Das; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
This study is concerned with the theory of parametric coupling of waves in a hot inhomogeneous magnetized plasma in which the temperature gradient has been taken into account. The general dispersion relation and the polarization of the ordinary and the extra-ordinary wave modes are discussed. The eigen-mode solutions of the coupled differential equations for the wave amplitudes are obtained in the terms of the so called three wave interaction matrix elements. The theory of nonlinear wave-wave interactions, which has been extended to the case of an inhomogeneous magnetized plasma, is used to determine the threshold value of the electric field and the frequency shift. The results of this paper are also compared with the other known results. It is shown that the findings of this study are in excellent agreement with the results of earlier investigators.